2019
DOI: 10.14639/0392-100x-2281
|View full text |Cite
|
Sign up to set email alerts
|

Brain abscess of odontogenic origin in children: a systematic review of the literature with emphasis on therapeutic aspects and a new case presentation

Abstract: SUMMARY Brain abscesses (BAs) are rare but life-threatening infections. BAs of an odontogenic origin should always be considered as a possible aetiological factor, especially when other infectious foci are not present. Clinical presentation in children may be ambiguous and pose a difficult differential diagnosis: the identification of causal bacteria can be difficult and odontogenic origin is often a diagnosis of exclusion. The aim of this paper was to systematically review the literature reports wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…12 A published systematic review of brain abscesses in children reported that an oral-maxillofacial examination should always be performed to exclude an oral origin. 13 In the case presented here, the history of the patient did not reveal anything specific; therefore, the port of entry of the bacteria could not be determined. Hematogenous spread could be considered as the cause, but the patient had no fever and blood cultures were sterile.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…12 A published systematic review of brain abscesses in children reported that an oral-maxillofacial examination should always be performed to exclude an oral origin. 13 In the case presented here, the history of the patient did not reveal anything specific; therefore, the port of entry of the bacteria could not be determined. Hematogenous spread could be considered as the cause, but the patient had no fever and blood cultures were sterile.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to the broad antibiotic treatment, incision and drainage of the abscesses were expressed to be more important than antibiotics alone in the management of Eikenella infections. 5 6 7 8 9 10 11 12 13 14 In recent years, although the prognosis has improved significantly with the development of additional diagnostic and therapeutic capabilities, neurological deficits can still be seen despite treatment and some children may need ventriculoperitoneal shunts. However, our patient did not have any neurological deficit after the treatment and the need for a shunt did not develop.…”
Section: Discussionmentioning
confidence: 99%
“…According to the review conducted by Moazzam et al regarding intracranial bacterial infections of oral origin, the hematogenous spread appears to be the more important pathophysiological route of spread. Most frequently the central nervous system infection is represented by an abscess (frontal lobe in 31.7 % of cases, parietal lobe in 21.7 % and temporal lobe in 13.7 %) while isolated meningitis resulted to be unusual (5 % of cases) (Moazzam et al, 2015;Lajolo et al, 2019). Moreover, they found that caries with periapical involvement and periodontitis are the oral pathologies most frequently responsible of an intracranial bacterial infection (Ewald et al, 2006;Moazzam et al).…”
Section: Discussionmentioning
confidence: 99%
“…20 Health awareness in terms of ear and oral hygiene may help to reduce the overall incidence of brain abscess. 51,52…”
Section: Preventionmentioning
confidence: 99%